PRONOMINA PERSONA BAHASA MELAYU RIAU SUBDIALEK BASERAH KECAMATAN KUANTAN HILIR KABUPATEN KUANTAN SINGINGI - Ovtaroza, Yulia Ovtaroza Yulia; AR, Hasnah Faizah AR Faizah; Hakim, Nursal Hakim Nursal (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract: Persona is the word personal pronouns a substitute who used to replace a word refers to persons.Persona of pronouns is also used by the community of Baserah in sub district of Kuantan Hilir, Kuantan SingingiRegency. One of the unique persona pronouns is the interpretation of it. One form of pronouns persona used in an area can have the level of civility a difference meaning in the place of another. Because of that , persona pronouns used in a society going to sound incongruous in the ear of people using other persona pronouns. The research is the qualitative study by the descriptive method.Of lab data in the form of oral speech classified based on its shape.The result of this research showed that persona the form of the personal pronouns in the malay language riau subdialek baserah consists of ( 1 ) the personal pronouns first persona ( 2 ) persona of pronouns second ( 3 ) the personal pronouns persona third.The personal pronouns third the persona divided more on the singular and plural.Based on its function persona the personal pronouns in the malay language Riau Subdialek Baserah can be used by someone who speaks substituting the name of its own one who talk to, and another person being talk about.The use of the personal pronouns each adapted to age, social status, and gender.Keyword: pronouns persona, shape, function